Effect of fragrance use on discrimination of individual body odor - Allen, Caroline; Havlíček, Jan; Roberts, S. Craig (Frontiers in Psychology, 2015)
Previous research suggests that artificial fragrances may be chosen to complement or enhance an individual’s body odor, rather than simply masking it, and that this may create an odor blend with an emergent quality that is perceptually distinguishable from body odor or fragrance alone. From this, it can be predicted that a new emergent odor might be more easily identified than an individual’s body odor in isolation. We used a triangle test paradigm to assess whether fragrance affects people’s ability to distinguish between individual odors. Six male and six female donors provided axillary odor samples in three conditions (without fragrance, wearing their own fragrance, and wearing an assigned fragrance). In total, 296 female and 131 male participants selected the odd one out from three odor samples (two from one donor, one from another; both of the same sex). We found that participants could discriminate between the odors at above chance levels in all three odour conditions. Olfactory identification ability (measured using Sniffin’ Sticks) positively predicted discrimination performance, and sex differences in performance were also observed, with female raters being correct more often than men. Success rates were also higher for odors of male donors. Additionally, while performance was above chance in all conditions, individual odor discrimination varied across the three conditions. Discrimination rate was significantly higher in the ‘no fragrance’ condition than either of the fragranced conditions. Importantly, however, discrimination rate was also significantly higher in the ‘own fragrance’ condition than the ‘assigned fragrance’ condition, suggesting that naturally occurring variance in body odor is more preserved when blended with fragrances that people choose for themselves, compared with other fragrances. Our data are consistent with the idea that fragrance choices are influenced by fragrance interactions with an individual’s own body odor.